A waste cooking oil-derived collector for enhanced selective flotation of hematite: From interfacial interaction to adsorption mechanism - Ruirui Zhang; Wengang Liu; Shuaichao Wang; Wenbao Liu (Minerals Engineering, 2026)

Evaluation and calculation of the 239Pu(n,f) cross section up to 200 MeV - Bo Gao; Changlin Lan; Bo Xie; Kuozhi Xu; Yanliang Chang; Muntazir Mehdi; Fanmin Zeng; Xiaonan Huang; Jianglong Pan; Ruirui Xu; Yue Zhang; Shilong Liu; et al. (Annals of Nuclear Energy, 2026)

Activating inert cobalt sites via interfacial nitrogen vacancies in Co3O4@g-C3N4 heterojunctions for selective boron recovery from hypersaline brines - Shao YiFan; Ruirui Liu; Yongquan Zhou; Jianming Pan (Water Research, 2026)

Dual-driven TBM attitude control method based on bidirectional mechanical control laws and tunneling parameter interaction - Jiwen Wang; Benchao Liu; Yaxu Wang; Ruirui Wang; Ningbo Li (Tunnelling and Underground Space Technology, 2026)

Numerical simulation of thermal-hydraulic-chemical multi-physical field coupling for large-scale experimental models of CO2 hydrate sequestration - Lei Wang; Xianjie Yan; Yang Ge; Ruirui Li; Zhaoran Wu; Jinyan Lan; Jiefeng Liu (Fuel, 2026)

Hydrological switching mechanism: Converting steep cropland to pasture mitigates nutrient loss by altering runoff pathways - Yanan Chen; Yuan Zhuang; Ruirui Yan; Peizhi Yang; Shimin Liu; Lianhai Wu; Yang Liu; Junbo Xiong; Jingwei Jin; Xiaoping Xin (CATENA, 2026)

1,12-cyclic-apelin-12 counters vascular smooth muscle cell proliferation and atherosclerosis through inhibiting aerobic glycolysis - Ruirui Lu; Xiaosi Zhou; Huimei Liu; Sisi Fan; Xiaohui Huang; Fengting Guo; Bin Huang; Linxi Chen; Lanfang Li (Toxicology and Applied Pharmacology, 2026)

Microalgae-based biogas slurry treatment integrated with sustainable aviation fuel production: from waste to high-value bio-jet fuel - Binbin Zhu; Hongyin Chen; Jing Lv; Wenjun Zhang; Jiaming Liu; Ruirui Liu; Bishu Qi; Shuhui Li; Chengyu Yang; Xiao Yan; Zijian Xia; Xingliang Xu; et al. (Bioresource Technology, 2026)

Historical grazing intensity determines the response patterns of plant community and soil nutrient stocks to grazing exclusion in a temperate meadow steppe - Haonan Guo; Xiaoping Xin; Jiquan Chen; Phil J. Murray; Maira Kussainova; Wei Fang; Zhigang Zhao; Hui Li; Cuixia Jiang; Yufan Si; Amarjargal Amartuvshin; Alim Pulatov; et al. (Agriculture, Ecosystems & Environment, 2026)

Mechanism and flotation performance of a phosphonic acid-based ionic liquid collector in Magnesite–Quartz separation - Ruirui Zhang; Wengang Liu; Shuaichao Wang (Minerals Engineering, 2026)

Trade-offs among pear yield, fruit quality, and reactive nitrogen losses under water–nitrogen management across contrasting soil textures - Yanlong Li; Ruirui Du; Mingde Sun; Yang Wu; Zhenxu Liang; Qinghua Wang; Jun Liu; Songzhong Liu (Journal of Environmental Management, 2026)

N and S co-doped graphene-based single-atom catalysts for highly efficient nitrate reduction - Jin-Hang Liu; Yu Sun; Xiaoduo Jiang; Huixiong Jiang; Ruirui Wang; Yawei Wang; Huixian Ye; Xiudong Chen; Li-Ming Yang (Fuel, 2026)

Coupling heterovalent complementary doping with surface tailoring for stable O3-type layered oxide cathodes - Yang Liu; Haoji Wang; Yang Sun; Yingchang Yang; Wei Shi; Kaixu Yang; Jing Chen; Ruirui Wang; Xinyao Yang; Yanxu Wang; Haibiao Ning; Qifu Shi; et al. (Chemical Engineering Journal, 2026)

Constructing atomic-scale proton channels in polymeric carbon nitride via synergistic oxygen and carbon defects for efficient CO2 photoreduction - Ruirui Wang; Yiming Wang; Jinhang Liu; Huixiong Jiang; Ran Wang; Yang Wang; Shunhang Wei; Xiaoxiang Xu; Yawei Wang (Chemical Engineering Journal, 2026)

Super-resolution multimodal spatial transcriptomics reveals an ovoid stem cell niche structuring de novo shoot regeneration - Xiehai Song; Shaoman Zhang; Zhiliang Yue; Yongqi Liu; Shanshan Chen; Yani Niu; Yan Shi; Hengjia Yang; Jiahao Xu; Yuanyuan Miao; Meizhi Xu; Yingxue Zhou; et al. (Molecular Plant, 2026)

Disaggregation mechanisms of asphaltenes induced by castor-based bio-oil: A molecular dynamics and rheological study - Tao Zhou; Ruirui Liu; Sainan Xie; Elham Fini; Zejiao Dong; Lingyun You (Fuel, 2026)

Indium-doped CuSnO3 perovskite hybrids for chemiresistive CO sensing - Linyan Gu; Yangtao Qian; Yiting Liu; Miao Cheng; Tao Wei; Qianqian Liu; Ruirui Wang; Wanfei Li; Zhenxiao Fu; Haiyang Jiang; Zibo Li; Bo Liu; et al. (Chemical Engineering Journal, 2026)

The pivotal regulatory factor circ_0006956 promotes arsenic-induced lung carcinogenesis by enhancing the Warburg effect - Deqing Li; Xiaodong Zhou; Dunyu Cai; Haotian Xu; Xingcai Chen; Shengyi Yuan; Taoran Ning; Xiangyu Dong; Mengyao Li; Qiumei Liu; Ruirui Zhang; Wenyi Peng; et al. (Chemico-Biological Interactions, 2026)

Investigation of the Degradation Mechanism of Dibutyl Phthalate in Soil Using Alkali-Modified Biochar and Persulfate Systems - Ruiling Zhang; Xinyu Zhang; Shuang Du; RuiRui Zhang; Jiayong Gao; Youjun Zhang; Jinpeng Liu (Water, Air, & Soil Pollution, 2026)

Metabolic engineering of mannitol metabolism to improve protein production in Fusarium venenatum - Xizhen Liu; Longxue Ma; Ruirui Zhang; Yang Yang; Wuxi Chen; Liucheng Long; Yu Zheng; Demao Li (Systems Microbiology and Biomanufacturing, 2026)

Fluoride-free separation of impurities from quartz sand via CaO-assisted hydrothermal activation and organic–inorganic acid leaching - Ruirui Zhang; Wengang Liu; Shuaichao Wang (Minerals Engineering, 2026)

Sustainable lithium extraction from low-grade aqueous resources via reverse Li/Mg separation enabled by hydrated cation-π interaction - Huixiong Jiang; Xing Liu; Jin-Hang Liu; Xiudong Chen; Ruirui Wang; Yawei Wang; Changchao Zhan; Xiaohua Cao; Xiushen Ye; Guosheng Shi (Journal of Cleaner Production, 2026)

Physics-informed neural network for predicting orbital parameters of Low Earth Orbit satellites using two line element dataset - Md Sahat Mahmud; Yiping Jiang; Ruirui Liu; Zihong Zhou; Bing Xu (Advances in Space Research, 2026)

Mechanistic study of macrolide antibiotics degradation induced by plasma-generated hydroxyl radicals and hydrogen peroxide - Ruirui Sun; Yifan Liu; Xiaolong Wang; Shiji Zhang; Daoyuan Liu; Zongzheng Wang; Yadi Liu; Ying Sun; Tong Zhao; Yuantao Zhang (Process Safety and Environmental Protection, 2026)

Catalytic liquefaction of pig manure in ethanol: Yield and properties of bio-oil - Qingdan Wu; Siyu Huang; Qianlan Li; Xiaochen Zheng; Wei Liu; Ruirui Zhu; Jialong Tang; Binbin Dai; Yingying Mo; Likun Zhan; Jie Xiong; Zhihua Xiao (Biomass and Bioenergy, 2026)

Clonidine compromises human sperm functions - Xuchang Liu; Yanfan Cui; Ruirui Qian; Yixuan Li; Zeyu Hu; Houyang Chen; Yufeng Yuan; Tao Luo (Reproductive Toxicology, 2026)

Distribution and source of plutonium in seawater columns of the oligotrophic region in the North Pacific - Ruirui Wang; Yukun Li; Deyu Wang; Xiaomin Wei; Yongjing Guan; Xibin Han; Zhiyong Liu (Marine Pollution Bulletin, 2026)

Effective bioremoval of Cu (II) and Sulfate from acid mine drainage via biomineralization with an extreme acidophile bacterium V. pantothenticus WL - Chao Han; Xiangwei Cheng; Zuozhen Han; Shourui Dai; Qingyuan Chen; Wen Nie; Yu Han; Haibo Zhu; Xiao Gao; Yanyang Zhao; Fang Liu; Maurice E. Tucker; et al. (Journal of Contaminant Hydrology, 2026)

Cuproptosis and Its Impact on Cardiovascular Health: Mechanisms and Therapeutic Opportunities - Xiaohui Huang; Liwen Wang; Huimei Liu; Ruirui Lu; Lanfang Li (Cardiovascular Toxicology, 2026)

mRNA Rather than Protein Expression of Hepatic Selenoprotein H is More Sensitive to Short-term Low Aflatoxin B1 Exposure in Mice with Varying Selenium Intake - Ruirui Yu; Mengru Hao; Aiping Liu; Chenggang Yang; Ping Xu; Yong Zhou; Alexey A. Tinkov; Aolin Yang; Qingqing Lv; Ziyu Han; Chao Wang; Zhou Wang; et al. (Biological Trace Element Research, 2026)

Identification of quantitative trait loci qPL6 for petiole length in soybean - Weiwei Fan; Lindong Wang; Wenxuan Huang; Jia Liu; Bing Li; Jingyu Peng; Ruirui Ma; Ran Xu; Lianjun Sun (Theoretical and Applied Genetics, 2026)

Changes in plant community composition and soil resource drive jointly fine root productivity response to grazing in a meadow steppe - Hui Li; Changliang Shao; Yuguang Ke; Xiaoping Xin; Ziwei Tao; Yufan Si; Haonan Guo; Cuixia Jiang; Ruirui Yan; Guozhen Du; Zihao Li; Feng Liu (Plant and Soil, 2026)

Corrigendum to “Anthropogenic and climate impacts on carbon stocks of grassland ecosystems in Inner Mongolia and adjacent region” [Sci. Total Environ. 946 (2024) 174054] - Xiaoping Xin; Linghao Li; HuaJun Tang; Haonan Guo; Hui Li; Cuixia Jiang; Feng Liu; Changliang Shao; Yifei Qin; Zhonglin Liu; Gele Qing; Ruirui Yan; et al. (Science of The Total Environment, 2025)

Bacterial communities of rhizolith- and root-associated in the Tengeri Desert, China - Jian Chen; Qingfeng Sun; Ruirui Chen; Zhihao Zhang; Zhen Liu; Gongyou Chen (Rhizosphere, 2025)

Corrosion characteristics of grate bars in complex sintering flue gas: Influencing factors and control measures - Xiaolong Wang; Zhiyun Ji; Min Gan; Xiaohui Fan; Gaige Zhao; Lincheng Liu; Hao Lv; Ruirui Yuan; Yufeng Wu (Process Safety and Environmental Protection, 2025)

The role of silica in biomass for calcium-modified biochar: Phosphorus removal mechanism and potential as a phosphate fertilizer application - Yongyi Chen; Ruiling Zhang; Jiayong Gao; Mujun Han; Songyan Qin; Kai Liu; Yajie Shu; Ruirui Zhang; Chang Shi; Yue Zheng (Journal of Environmental Sciences, 2025)

Exploration of the Lactiplantibacillus pentosus genetic diversity and its antibacterial properties based on comparative genome - Lixia Zhao; Ruirui Lv; Wenjun Liu (Food Bioscience, 2025)

Unveiling the oxidation-reduction mechanism of the Arsenazo III-U(VI) complexes by synergistic electron beam irradiation and Cu-Fe MOFs: Combined kinetic and DFT studies - Ruirui Wang; Xiaomao Zhou; Dan Liu; Jiahui Li; Long Zhao; Zhen Dong; Buri Qi; Miao Yang (Chemical Engineering Journal, 2025)

Starch branching enzyme: structure, key functional sites, and regulation of starch characteristics and rice qualities - Minxue Ke; Ruirui Liu; Renying Wu; Cunxu Wei (Plant Cell Reports, 2025)

Benchmark testing for 2H neutron cross section calculated using Faddeev equation - Huanyu Zhang; Haicheng Wu; Ruirui Xu; Ping Liu; Xiaofei Wu; Xiaodong Sun; Danyang Pang (Annals of Nuclear Energy, 2025)

Effects of Zygosaccharomyces rouxii on metabolites and volatile substances during the fermentation of jujube beverage based on LC-MS, HS-GC-IMS and ET analysis - Peixing Ren; Xiaojing Zheng; Ruirui Dao; Jia Tian; Shuang Wu; Hanbing Zhu; Lili Wang; Mengjun Liu; Zhihui Zhao (Food Chemistry, 2025)

Evaluation of the Degradation Effect of Zearalenone in feed by Bacillus amyloliquefaciens H6 and its Detoxification in Mice - Ruolin Wang; Kaiwei Geng; Yuxuan Liu; Yang Liu; Yujie Gong; Ruirui Jiang; Yadong Tian; Xiangtao Kang; Xiangli Sun; Yanbin Wang (Current Microbiology, 2025)

National-scale genomic diagnosis of rare diseases in China - Xiaodong Luan; Ye Jin; Liping Guan; Peng Liu; Hailong Feng; Dingding Zhang; Jingdan Chen; Weida Liu; Fangyuan Li; Anqi Wang; Kun Zhao; Ruirui He; et al. (Science Bulletin, 2025)

Selective and efficient adsorption of H3BO3 from Salt Lake brine solution by ZIF-67-derived hollow cobalt sulfide - Yifan Shao; Chao Hu; Ruirui Liu; Bingxin Liu; Yongquan Zhou; Jianming Pan (Desalination, 2025)

Reineckeacarnisides A and B, two new saponins from Reineckea carnea - Ping Wang; Feiyu Liao; Hongqian Liu; Ruirui Zhang (Natural Product Research, 2025)

Integration of warm mix technology and high crumb rubber content for enhanced asphalt treated base material - Tao Zhou; Ruirui Liu; Liping Cao; Chenguang Jin; Zejiao Dong; Abaho G. Gershome; Qilin Huang (Journal of Cleaner Production, 2025)

Engineering Komagataella phaffii cell factories for the production of chondroitin sulfate A with high sulfation degree - Haibo Xiong; Xiaogang Yang; Weijiao Zhang; Litao Hu; Gege Liu; Guocheng Du; Jian Chen; Jianghua Li; Ruirui Xu; Zhen Kang (Chemical Engineering Journal, 2025)

Dual AIE combination strategy: An efficient BioAIE active photosensitizer derived from berberine for bacterial elimination - Zhi-Hao Li; Daran Li; Yuanbo Li; Ruirui Li; Hongtao Kong; Ye Qu; Yuequan Wu; Jifeng Liu; Shangshang Qin; En Zhang; Yong-Qiang Tu (Chemical Engineering Journal, 2025)

“Vacancy mediated internal-external synergy” regulation strategy on constructing defect-engineered non-noble metal catalysts for electrooxidation of glycerol - Sheng Zhong; Syed Ali Haider Zaidi; Bin He; Shuang Wei; Hasnain Nawaz; Ruirui Wang; Ruixia Liu (Chemical Engineering Journal, 2025)

Impact of micro- and nano-plastics on marine organisms under environmentally relevant conditions - Ruirui Wang; Hongmei Tan; Xiaochen Huang; Jianjun Wang; Wenli Su; Farhana Maqbool; Lu Liu; Yuanshuo Ma; Meng Wang; Zhuomiao Liu; Xia Liu; Yanhui Dai; et al. (Aquatic Toxicology, 2025)

Establishment of reference intervals for serum immunoglobulin G N-glycosylation features in healthy Chinese adults: a nationwide survey in the framework of predictive, preventive, and personalized medicine - Changyu Liu; Yinghao Wang; Xingang Li; Xiaojia Xu; Ruirui Xu; Cuihong Tian; Zhixian Chen; Xinxia Lu; Yuejin Li; Meng Wang; Zhaoyang Tang; Xueyu Chen; et al. (EPMA Journal, 2025)

A new strategy of one-step sequential extraction of copper cyanide complex ions from cyanide leach solutions - Weichao Li; Wengang Liu; Wenbao Liu; Ruirui Zhang; Shuaichao Wang (Minerals Engineering, 2025)

Meat quality differences and protein molecular mechanisms affecting meat flavor in different breeds of Tibetan sheep analyzed by 4D label-free quantitative proteomics - Jianfeng Xu; CailianWang; Ting Liu; Ruirui Luo; Chen Zheng; Yanshu Zhang; Xia Lang (Food Chemistry, 2025)

High-efficiency and stable perovskite solar cells via bidentate chelation for facet-engineered growth of FAPbI3 (111) crystals - Song Zhang; Yucong Zhou; Zhitao Shen; Yingying Li; Jian Song; Yicong Gao; Zezhi Wang; Bohao Zhang; Chong Chen; Rong Liu; Ying Liu; Ruirui Cao; et al. (Chemical Engineering Journal, 2025)

Long-term reconstruction of NO2 photolysis rate coefficients using machine learning and its impact on secondary pollution: A case study in a megacity of the Sichuan Basin, China - Tong Li; Song Liu; Dongyang Chen; Ruirui Zhang; Hefan Liu; Danlin Song; Qinwen Tan; Hongbin Jiang; Li Zhou; Fumo Yang (Atmospheric Pollution Research, 2025)

A genomic compendium of cultivated food-derived lactic acid bacteria unveils their contributions to human health - Hao Jin; Keyu Quan; Lijun You; Lai-Yu Kwok; Teng Ma; Yalin Li; Xuan Shi; Xin Su; Ruirui Lv; Zhihong Sun; Wenjun Liu; Heping Zhang (Science Bulletin, 2025)

Short-term PS-NP exposure in early adulthood induces neuronal damage in middle-aged mice via microglia-mediated neuroinflammation - Shan Shan; Dong Cheng; Hui Li; Wenhuan Yao; Ruirui Kou; Jing Ji; Na Liu; Tao Zeng; Xiulan Zhao (Journal of Hazardous Materials, 2025)

The novel biochar-based organic semiconductor toward broadband and direct radicals transfer enhanced photocatalytic degradations - Yuchen Wang; Qianqian Pan; Songlin Cai; Liwei Liang; Liangsheng Chen; Ruirui Zhang; Liu Liu; Yanzhen Yin; Tao Yang; Hongxiang Zhu; Tao Liu (Journal of Environmental Management, 2025)

Layered double hydroxides-engineered biochar for selective phosphate recovery by flow-electrode capacitive deionization - Jingke Song; Xin Zhao; Ruirui Liu; Songsong Zhi; Ruixue Han; Jiangzhou Xie; Jianhui Sun; Kai Jiang; Dapeng Wu (Journal of Environmental Chemical Engineering, 2025)

Involvement of the miR156/SPLs/NLP7 modules in plant lateral root development and nitrogen uptake - Ruirui Xu; Peng Wang; Yunning Pang; Huilian Liu; Tianpeng Zhang; Ying Li; Shizhong Zhang (Planta, 2025)

Identification of biomarkers associated with phagocytosis regulatory factors in coronary artery disease using machine learning and network analysis - Runan Jia; Zhiya Li; Yingying Du; Huixian Liu; Ruirui Liang (Mammalian Genome, 2025)

Nonlinear interactions of internal waves and the force of internal solitary waves on small - Diameter cylinders - Qian Liu; Zhao Song; Huan Mei; Ruirui Zhang; Zhenzhen Nong; Daiyu Zhang (Ocean Engineering, 2025)

Quercetin attenuates DEHP-induced pyroptosis and programmed necrosis in chicken duodenum through regulation of the TLR4/MyD88/NF-κB pathway - Ruirui Xie; Tong Xu; Yilin Yin; Meichen Liu; Chenxi Huang; Wenwen Zhang; Shu Li (Environmental Pollution, 2025)

Highly synergistic degradation of norfloxacin and outstanding elimination of antibiotic-resistant elements by a combined electro-Fenton/peracetic acid process under mild conditions - Ling Feng; Wentao Dong; Bowei Li; Qing Li; Zhijing Liu; Ruirui Feng; Stefanos Giannakis (Journal of Environmental Chemical Engineering, 2025)

The dynamics impact of phlorizin on gut microbiota and metabolites in an in vitro fermentation model - Dingzuo Ge; Luyao Zheng; Li Liu; Xin Chen; Jiawei Zhou; Han Ge; Liqiang Guo; Hua Hua; Ruirui Wang; Lei Zhang (Food Research International, 2025)

Warmer summers have the potential to affect food security by increasing the prevalence and activity of Actinobacteria - Yuanyuan Bao; Jan Dolfing; Zhiying Guo; Jie Liu; Xianzhang Pan; Xiaodan Cui; Yuanyuan Wang; Yang Jin; Lixia Zhang; Ruirui Chen; Xin Li; Youzhi Feng (European Journal of Soil Biology, 2025)

Screening of Herbicides and Disturbance Effects upon Use of Benzonitrile Herbicide BOMS on Soil Microecology in Oat Field - Huan Liu; Jennifer Schug; Changning Li; Ruirui Yao; Guiqin Zhao; Yujie Niu (Journal of Soil Science and Plant Nutrition, 2025)

Airway exposure to lithium nickel manganese cobalt oxide particles induces alterations in lung microenvironment and potential kidney and liver damage in mice - Junyi Wang; Xin Fang; Ruirui Wu; Ziyu Liu; Gang Wang; Yuxin Hu; Huihui Wang; Jingbo Pi; Yuanyuan Xu (Toxicology, 2025)

An innovative process for two-step leaching calcium from steel slag and capturing CO2 to synthesize spindle-shaped CaCO3 - Min Gan; Lincheng Liu; Zengqing Sun; Xiaohui Fan; Zitan Gao; Zhiyun Ji; Ruirui Yuan; Yufeng Wu; Xiaolong Wang; Hao Lv; Yuncan Cao (Process Safety and Environmental Protection, 2025)

A bifunctional MXene@PtPd NPs cascade DNAzyme-mediated fluorescence/colorimetric dual-mode biosensor for Pb2+ determination - Zhiguang Suo; Liuyi Zhang; Zhen Zhang; Ruirui Liang; Hailin Shen; Xiaohui Chen; Yong Liu; Min Wei; Baoshan He; Huali Jin (Food Chemistry, 2025)

Bimetallic Bi–Sn nanoparticles in-situ anchored in carbon nanofiber as flexible self-supporting anode toward advanced magnesium ion batteries - Shaoqing Pan; Miao Cheng; Chen Ma; Huaijia Jing; Tongyu Shen; Jing Hu; Qianqian Liu; Tao Wei; Ruirui Wang; Wanfei Li; Bo Liu (Chemical Engineering Journal, 2025)

Selective oxidation of 2-methoxycyclohexanone to monomethyl adipate catalyzed by acidic ionic liquids - Yumei Liu; Kexin Li; Hasnain Nawaz; Ruirui Zhang; Min Ji; Ruixia Liu (Chemical Engineering Journal, 2025)

Knocking Down HN1 Blocks Helicobacter pylori-Induced Malignant Phenotypes in Gastric Mucosal Cells and Inhibits Gastric Cancer Cell Proliferation, Cytoskeleton Remodeling, and Migration - Ying Huang; Xiaofei Wang; Hao Liu; Xiangkun Meng; Hua Yin; Ruirui Hou; Wan Lin; Xu Zhang; Jun Ma; Xiaoxu Zhang; Feixiong Zhang; Yu Miao (Biochemical Genetics, 2025)

Carbonation pretreatment enhance the hydrothermal detoxification of municipal solid waste incineration fly ash - Ruirui Yuan; Xiaohui Fan; Min Gan; Zhiyun Ji; Zengqing Sun; Lincheng Liu; Xiaolong Wang; Jiaoyang Wei (Process Safety and Environmental Protection, 2025)

Comparisons of filter, wrapper, and embedded feature selection for rockfall susceptibility prediction and mapping - Chengming Lei; Chunyan Liu; Yunbin Zhang; Jianmei Cheng; Ruirui Zhao (Natural Hazards, 2025)

Electron beam irradiation in collaboration with Bi-Fe MOFs for oxidation of bisphenol A and reduction of Cr(VI): Kinetics, DFT calculation and mechanism - Dan Liu; Junhui He; Ruirui Wang; Zhen Zhao; Zhen Dong; Qiburi Bao; Long Zhao; Miao Yang (Journal of Environmental Chemical Engineering, 2024)

A comparative study of low-cost crude ureases extracted from multi-species of natural plant sources in enzyme-induced carbonate precipitation - Lingxiao Liu; Yaqing Gao; Xinwen Cao; Hao Meng; Zhanbin Wang; Yongshuai Qi; Ruirui Li; Jia He (Journal of Environmental Chemical Engineering, 2024)

Impacts of forest restoration on multifaceted bird diversity and community assembly in the Loess Plateau of China - Dexi Zhang; Ruirui Mao; Mingxin Liu; Qian Zhou; Yizhu Wang; Xingfeng Si; Changming Zhao; Lixun Zhang (Forest Ecology and Management, 2024)

A highly sensitive electrochemical immunosensor based on rGO-PEI-Ag nanocomposites for the detection of tilmicosin - Yumei Chen; Jialin Zhang; RuiRui Liu; Ying Zhang; Jingming Zhou; Hongliang Liu; Yankai Liu; Ke Yan; Yanhua Qi; Enping Liu; Xifang Zhu; Aiping Wang (Food Chemistry, 2024)

Urea amidolyase displayed on the surface of Saccharomyces cerevisiae for ethyl carbamate reduction in Chinese Huangjiu - Yupeng Wang; Qingbo Deng; Fangyuan Liu; Qian Li; Ruirui Li; Huan Wang; Chunhong Sun; Xinjian Wang; Xiaole Wu; Yefu Chen (Food Control, 2024)

Targeting STING oligomerization with licochalcone D ameliorates STING-driven inflammatory diseases - Yinghui Zhang; Yadan Liu; Bing Jiang; Lifan Chen; Jie Hu; Buying Niu; Jie Chang; Zisheng Fan; Jingyi Zhou; Yajie Wang; Dan Teng; Ning Ma; et al. (Science China Life Sciences, 2024)

Nuclear data processing and benchmarking for the test edition of China evaluated photonuclear data library (CENDL/PD-b) - Ping Liu; Huanyu Zhang; Xiaofei Wu; Ruirui Xu; Xi Tao; Yuan Tian; Yongli Jin; Jimin Wang; Zhi Zhang; Zhigang Ge; Nengchuan Shu (Annals of Nuclear Energy, 2024)

From expansion to efficiency: Machine learning-based forecasting of Japan's building material stocks under demographic declines - Lei Wang; Ruirui Zhang; Zhiwei Liu; Hiroaki Shirakawa; Hiroki Tanikawa (Science of The Total Environment, 2024)

Quercetin attenuates SiO2-induced ZBP-1-mediated PANoptosis in mouse neuronal cells via the ROS/TLR4/NF-κb pathway - Meichen Liu; Meichen Gao; Xu Shi; Yilin Yin; Huanyi Liu; Ruirui Xie; Chenxi Huang; Wenwen Zhang; Shiwen Xu (Journal of Environmental Management, 2024)

Dissolved ammonia catalyzes proto-dolomite precipitation at Earth surface temperature - Ruirui Meng; Zuozhen Han; Xiao Gao; Yanyang Zhao; Chao Han; Yu Han; Renchao Yang; Shuangjian Li; Fang Liu; Maurice E. Tucker; Yanjing Chen (Earth and Planetary Science Letters, 2024)

Tilletia laevis caused common bunt disease of wheat in district Swat, Khyber Pakhtunkhwa-Pakistan - Chen Delai; Ghulam Muhae-Ud-Din; Liu Ruirui; Liu Zicheng; Ma Shirong (Crop Protection, 2024)

Anthropogenic and climate impacts on carbon stocks of grassland ecosystems in Inner Mongolia and adjacent region - Xiaoping Xin; Xueqi Lan; Linghao Li; HuaJun Tang; Haonan Guo; Hui Li; Cuixia Jiang; Feng Liu; Changliang Shao; Yifei Qin; Zhonglin Liu; Gele Qing; et al. (Science of The Total Environment, 2024)

Coordination-regulated epitaxial growth for 2D/3D perovskite vertical alignment heterostructure - Guoxiang Zhao; Yuan Chen; Shan Cong; Lutao Li; Chen Wang; Xinyu Du; Ruirui Liu; Jing Lu; Yu Liu; Gaoyuan Chen; Sihan Zhang; Liya Zhang; et al. (Science Bulletin, 2024)

Efficient extraction of lithium from alkaline solution using the synergistic extractants ethylhexyl salicylate and trialkylphosphine oxide in kerosene and stripping with acid - Zhonghua Niu; Licheng Zhang; Ruirui Liu; Yongquan Zhou; Lianmin Ji; Lijuan Li (Hydrometallurgy, 2024)

Microbial Community Structure and Metabolism of Xinjiang Fine-Wool Sheep based on High-Throughput Sequencing Technology - Rui Yao; Fulin Li; Xuyang Dong; Yueren Xu; Ruirui Hu; Limin Wang; Kuojun Cai; Xiaogang Liu; Wei Ni; Ping Zhou; Shengwei Hu (Current Microbiology, 2024)

Zirconium‑cerium modified polyvinyl alcohol/NaCMC biocomposite film: Synthesis of films through high-speed shear assisted technique and removal fluoride from water - Ruirui Yang; Fuqing Bai; Liping Mei; Wei Guo; Huanhuan Qiao; Guijie Chen; Junsheng Liu; Fei Ke; Chuanyi Peng; Ruyan Hou; Xiaochun Wan; Huimei Cai (Carbohydrate Polymers, 2024)

Synthesis, structure-activity relationship and evaluation of antifungal activity of tryptanthrin derivatives against drug-resistant Candida albicans - Yandan Wu; Luyi Jiang; Ruina Liu; Lijiao Yang; Fei Zou; Tianyu Zhang; Zefei Fan; Tianbao Zhang; Huan Yang; Shuyun Yin; Ruirui Wang; Ganpeng Li; et al. (Medicinal Chemistry Research, 2024)

Screening and identification of reactive metabolic compounds of Cortex Periplocae based on glutathione capture-mass spectrometry - Guantong Yu; Ruirui Wang; Xiaomei Liu; Yuhong Li; Lin Li; Xiaoming Wang; Yuhong Huang; Guixiang Pan (Journal of Natural Medicines, 2024)

Construction of immobilized enzyme cascades for the biosynthesis of nucleotide sugars UDP-N-acetylglucosamine and UDP-glucuronic acid - Jialian Li; Yanlai Liu; Litao Hu; Ruirui Xu; Weijiao Zhang; Shan Hu; Yang Wang; Guocheng Du; Zhen Kang (Systems Microbiology and Biomanufacturing, 2024)

Understanding the effect of plastic food packaging materials on food flavor: A critical review - Fuqing Bai; Guijie Chen; Yanan Hu; Yuexin Liu; Ruirui Yang; Junsheng Liu; Ruyan Hou; Hongfang Li; Xiaochun Wan; Huimei Cai (Trends in Food Science & Technology, 2024)

Interfacial hydrogen bond effect between CeO2 and g-C3N4 boosts conversion to adipic acid from aerobic oxidation of cyclohexane - Kexin Li; Bin He; Ruirui Wang; Ruiyi Yan; Ruirui Zhang; Ruixia Liu (Chemical Engineering Journal, 2024)

Enhanced the dehydrocyclization of 1,4-butanediol to γ-butyrolactone via the regulation of interface oxygen vacancies in Cu/MgO-CeO2 catalyst - Siying Chong; Shuang Zhao; Jiaoyan Li; Gangwei Huang; Yajing Zhang; Ruirui Liu; Kangjun Wang (Chemical Engineering Journal, 2024)

Shared xerophytic genes and their re‐use in local adaptation to aridity in the desert plant Gymnocarpos przewalskii - Ruirui Fu; Yuxiang Zhu; Ying Liu; Zhaoping Yang; Ruisen Lu; Yingxiong Qiu; Martin Lascoux; Pan Li; Jun Chen (Molecular Ecology, 2024)
In order to thrive and survive, plant species need to combine stability in the long term and rapid response to environmental challenges in the short term. The former would be reflected by parallel or convergent adaptation across species, and the latter by pronounced local adaptation among populations of the same species. In the present study, we generated a high‐quality genome and re‐sequenced 177 individuals for Gymnocarpos przewalskii , an important desert plant species from North‐West China, to detect local adaptation. We first focus on ancient adaptation to aridity at the molecular level by comparing the genomic data of 15 species that vary in their ability to withstand aridity. We found that a total of 118 genes were shared across xerophytic species but absent from non‐xerophytic species. Of the 65 found in G. przewalskii , 63 were under purifying selection and two under positive selection. We then focused on local adaptation. Up to 20% of the G. przewalskii genome showed signatures of local adaptation to aridity during population divergence. Thirteen of the selected shared xerophytic genes were reused in local adaptation after population differentiation. Hence, only about 20% of the genes shared and specific to xerophytic species and associated with adaptation to aridity were later recruited for local adaptation in G. przewalskii .

Thermal effects on rheological characteristics and its evolution mechanism of bio-modified rubberized asphalt for sustainable road system: A focus on rubber particle size - Tao Zhou; Lingwen Li; Ruirui Liu; Fangzhou Yu; Zejiao Dong (Journal of Cleaner Production, 2024)

Unearthing the global patterns of cultural heritage microbiome for conservation - Yongjie Yu; Jianwei Zhang; Ruirui Chen; Claudia Coleine; Wenjing Liu; Manuel Delgado-Baquerizo; Youzhi Feng (International Biodeterioration & Biodegradation, 2024)

Rare earth cation-modified X zeolites for isobutane alkylation: The influence of ionic radius - Zhiqiang Yang; Xinxin Li; Ruirui Zhang; Ruixia Liu (Fuel, 2024)

Metal coordination center mediated microenvironment regulation of cobalt sites on poly(ionic liquid)s enhance selective oxidation of cyclohexane conversion - Shengxin Chen; Bin He; Yingwei Li; Ruirui Wang; Ping Chen; Xingang Li; Ruixia Liu (Chemical Engineering Journal, 2024)

Systematic Analysis of the Relationship Between Elevated Zinc and Epilepsy - Dadong Luo; Yaqing Liu; Junqiang Li; Xuhui Liu; Ruirui Zhang; Xuejuan Liu; Ningning Zhang; Wenzhao Zhang; Jiayi Liu; Lan Zhang; Tiancheng Wang (Journal of Molecular Neuroscience, 2024)

Effects of natural sound exposure on health recovery: A systematic review and meta-analysis - Ruirui Zhu; Liyun Yuan; Yanting Pan; Yefan Wang; Danping Xiu; Weiyi Liu (Science of The Total Environment, 2024)

Mg Fe- layered double hydroxides (LDHs) modified electrode enhanced capacitive deionization for simultaneous phosphorus recovery and copper ions removal - Jingke Song; Chenyang Li; Xin Zhao; Ruirui Liu; Ruixue Han; Kai Jiang; Meiqing Shi; Dapeng Wu (Journal of Environmental Chemical Engineering, 2024)

Geological structure identification of coalbed methane reservoir based on trend surface and curvature analysis algorithms - Guoxu Chen; Ruirui Li; Li Cao; Fang Lv; Jing Yuan; Panpan Li; Shengdong Liu; Zhongcheng Li (Earth Science Informatics, 2024)

Urban green space area mitigates the accumulation of heavy metals in urban soils - Shuhong Luo; Ruirui Chen; Jigang Han; Weiwei Zhang; Evangelos Petropoulos; Yun Liu; Youzhi Feng (Chemosphere, 2024)

Toward a remote sensing method based on commercial LiDAR sensors for the measurement of spray drift and potential drift reduction - Longlong Li; Ruirui Zhang; Liping Chen; Andrew J. Hewitt; Xiongkui He; Chenchen Ding; Qing Tang; Boqin Liu (Science of The Total Environment, 2024)

Construction of potassium cobalt iron cyanide double-hollow nanobubble prisms for high selective adsorption of cesium - Hangyu Wang; Chao Hu; Yifa Du; Ruirui Liu; Zhong Liu; Li Han; Yongquan Zhou (Journal of Water Process Engineering, 2024)

Isolation methods, proliferation, and adipogenic differentiation of adipose-derived stem cells from different fat depots in bovines - Ruirui Zhu; Ye Feng; Ruirui Li; Kelong Wei; Yun Ma; Qingyou Liu; Deshun Shi; Jieping Huang (Molecular and Cellular Biochemistry, 2024)

ERS Mediated by GRP-78/PERK/CHOP Signaling Is Involved in Fluoride-Induced Ameloblast Apoptosis - Li Jinyi; Yang Keyu; Dai Shanshan; He Shuyang; Liu Ruirui; Guo Qingyu; Liu Fei (Biological Trace Element Research, 2024)

A nested case-control study of serum zinc and incident diabetes among Chinese adults: Effect modifications and mediation analysis - Jingli Yang; Zhiyuan Cheng; Desheng Zhang; Tongzhang Zheng; Chun Yin; Simin Liu; Lizhen Zhang; Zhongge Wang; Yufeng Wang; Ruirui Chen; Qian Dou; Yana Bai (Science of The Total Environment, 2024)

Advancing sustainability with inverse vulcanization of waste sulfur catalyzed with TiO2 - Masoumeh Mousavi; Tao Zhou; Ruirui Liu; Zejiao Dong; Elham H. Fini (Journal of Environmental Chemical Engineering, 2024)

Ionic liquids assisted synthesis of graphite carbon nitride for one-pot aerobic oxidation of cyclohexane to adipic acid - Kexin Li; Shuang Wei; Yumei Liu; Ruirui Wang; Ruirui Zhang; Ruixia Liu (Chemical Engineering Journal, 2024)

A magnetic pore-confined catalyst with ionic liquids supported on MOFs for the synthesis of aryl-oxazolidinones: design, performance, and recyclability - Siying Chong; Jiaoyan Li; Shuang Zhao; Gangwei Huang; Yajing Zhang; Ruirui Liu; Kangjun Wang (Chemical Engineering Journal, 2024)

Reliability service-based strategies for improving electricity retailer competitiveness using a novel heuristic algorithm - Jichun Liu; Ruirui Huang; Xiao Xu; Yuyan Yang; Junyong Liu (Journal of Cleaner Production, 2024)

Eco-friendly synthesis of chemically cross-linked chitosan/cellulose nanocrystal/CMK-3 aerogel based shape-stable phase change material with enhanced energy conversion and storage - Miao Cheng; Yifan Yuan; Huaijia Jing; Jing Hu; Qianqian Liu; Tao Wei; Ruirui Wang; Wanfei Li; Bo Liu (Carbohydrate Polymers, 2024)

Single-step hydrothermal synthesis of biochar from waste industrial hemp stalk core for Pb2+ sorption: Characterization and mechanism studies - Zheren Zhang; Nengsheng Liu; Xiang Li; Yunzhu Wang; Yongkang Xiong; Ruirui Meng; Le Liu; Sufang He (Sustainable Chemistry and Pharmacy, 2023)

Paving the way to the future: Mapping historical patterns and future trends of road material stock in Japan - Ruirui Zhang; Naho Yamashita; Zhiwei Liu; Jing Guo; Yuki Hiruta; Hiroaki Shirakawa; Hiroki Tanikawa (Science of The Total Environment, 2023)

Do climate policy uncertainty and investor sentiment drive the dynamic spillovers among green finance markets? - Ruirui Wu; Bing-Yue Liu (Journal of Environmental Management, 2023)

Using UAV-based multispectral remote sensing imagery combined with DRIS method to diagnose leaf nitrogen nutrition status in a fertigated apple orchard - Guangzhao Sun; Tiantian Hu; Shuaihong Chen; Jianxi Sun; Jun Zhang; Ruirui Ye; Shaowu Zhang; Jie Liu (Precision Agriculture, 2023)

Intraspecific microdiversity and ecological drivers of lactic acid bacteria in naturally fermented milk ecosystem - Lijun You; Hao Jin; Lai-Yu Kwok; Ruirui Lv; Zhixin Zhao; Menghe Bilige; Zhihong Sun; Wenjun Liu; Heping Zhang (Science Bulletin, 2023)

Rapid discrimination of the identity of infant formula by triple-channel models - Nasi Ai; Ruirui Liu; Xuelu Chi; Zheng Song; Yiwei Shao; Yanmei Xi; Tong Zhao; Baoguo Sun; Jianbo Xiao; Jianjun Deng (Food Chemistry, 2023)

Discovery of deguelin derivatives in combination with fluconazole against drug-resistant Candida albicans - Biaoqi Liu; Youwei Wu; Dingmei Qin; Hairong Wang; Hongjie Chen; Yi Zhang; Weilie Xiao; Xiaoli Li; Ruirui Wang; Ruihan Zhang (Medicinal Chemistry Research, 2023)

CoupleUNet: Swin Transformer coupling CNNs makes strong contextual encoders for VHR image road extraction - Ruirui Li; Tao Chen; Yiran Liu; Haoyu Jiang (International Journal of Remote Sensing, 2023)

Synergistic effect of multi-phase and multi-domain structures induced high energy storage performances under low electric fields in Na0.5Bi0.5TiO3-based lead-free ceramics - Pu Mao; Yongguang Guo; Gang Lu; Qingsong Yan; Ruirui Kang; Ting Wang; Bing Xie; Zhiyong Liu; Lixue Zhang (Chemical Engineering Journal, 2023)

Synthetic bacterial communities reshape microbial communities and enhance nutrient supply in desertified land of Northwest China - Xinwei Hao; Xiao Wang; Chunlei Chen; Ruirui Liu; Yanling Yin; Jun Yao; Zhibo Xiao; Xiaozhen Liu; Xihui Shen; Xingyu Liu (Applied Soil Ecology, 2023)

Fabrication and application of molecularly imprinted polymer doped carbon dots coated silica stationary phase - Peijun Chai; Xuhui Geng; Ruirui Zhu; Wenpu Wu; Xuesong Wang; Jinhua Li; Longwen Fu; Hongdan Wang; Wanhui Liu; Lingxin Chen; Zhihua Song (Analytica Chimica Acta, 2023)

Degradation of 2,4-Dichlorophenol Through Fenton Process Catalyzed by Nanoscale Zero-Valent Iron Supported by Biochar - Junlong Yu; Xiuxia Zhang; Ruojun Ma; Yi Du; Xiaodong Zhao; Shuai Zuo; Kangning Dong; Ruirui Wang; Yupeng Zhang; Yingying Gu; Juan Sun; Qiyou Liu (Water, Air, & Soil Pollution, 2023)

Genetic analysis and QTL mapping for silique density in rapeseed (Brassica napus L.) - Xingrong Ma; Jinhua Wang; Yongfen Gu; Pengpeng Fang; Wenjing Nie; Ruirui Luo; Jin Liu; Wei Qian; Jiaqin Mei (Theoretical and Applied Genetics, 2023)

Flexible stretchable SEBS/n-alkane phase change composite films for highly efficient thermal management and infrared stealth applications - Yangjiu Zhao; Shaowei Shen; Xinya Wang; Ruirui Cao; Xiaoyong Jia; Xiling Niu; Haihui Liu; Xingxiang Zhang (Energy and Buildings, 2023)

Morphology and location of sensilla in the antennae and ovipositor of Sirex noctilio (Hymenoptera: Siricidae) - Enhua Hao; Rui Liu; Ruirui Xu; Pengfei Lu; Haili Qiao (Arthropod Structure & Development, 2023)

A novel protein domain is important for photosystem II complex assembly and photoautotrophic growth in angiosperms - Wei Li; Jiangfan Guo; Xue Han; Xiaowen Da; Kai Wang; Hongfei Zhao; Shi-Tang Huang; Bosheng Li; Hang He; Ruirui Jiang; Shichen Zhou; Peng Yan; et al. (Molecular Plant, 2023)

Spatial–temporal dynamics of the built environment toward sustainability: A material stock and flow analysis in Chinese new and old urban areas - Dong Yang; Mengyuan Dang; Jing Guo; Lingwen Sun; Ruirui Zhang; Feng Han; Feng Shi; Qian Liu; Hiroki Tanikawa (Journal of Industrial Ecology, 2023)
The urban built environment has accumulated massive amounts of resources, which is the main “hot spot” of construction materials and energy consumption in cities. To effectively monitor and manage resources use and waste disposal toward sustainability, this study intended to explore different metabolic paths of the urban built environment, as well as strategies for new and old urban areas separately with the help of material stock and flow analysis. Based on snapshots of 2003, 2010, and 2017 and combined with big data, a four‐dimensional geographic information system buildings database of Lixia District in Jinan, China, was compiled for bottom‐up stock modeling. Finally, the environmental impact assessment of the buildings’ demolition and disposal stage was carried out. The results showed that the building material stock was 142.31 Mt in 2017, with an increase of 69% from 2003. The reinforced concrete buildings increased rapidly from 2003 to 2017, especially in new urban areas, which has boosted demand for steel and cement by more than 150% during these 15 years. The material stock of the old urban area tends to be saturated, whereas the new urban area has experienced a rapid expansion with the material inflow four times as large as the material outflow. Potential recycling of waste concrete can reduce the generation of building demolition waste by 50%, save 0.15 km 2 of land occupation, increase raw material substitution by nearly 10 times, and reduce CO 2 emissions by 2.5 times.

TBM penetration rate prediction ensemble model based on full-scale linear cutting test - Yaxu Wang; Jiwen Wang; Ruirui Wang; Bin Liu; Yao Li (Tunnelling and Underground Space Technology, 2023)

Has the healthy city pilot policy improved urban health development performance in China? Evidence from a quasi-natural experiment - Yujie Wang; Ruirui Pei; Xiao Gu; Bei Liu; Lin Liu (Sustainable Cities and Society, 2023)

Bionic morphological design and interface-free fabrication of halfmoon microrobots with enhanced motion performance - Dong Liu; Dayin Sun; Jiaxin Zhou; Haoran Liu; Ruirui Guo; Bin Wang; Wenjun Ma; Zhenzhong Yang; Yuan Lu (Chemical Engineering Journal, 2023)

A convenient paper-based fluorescent aptasensor for high-throughput detection of Pb2+ in multiple real samples (water-soil-food) - Zhiguang Suo; Ruirui Liang; Ruike Liu; Min Wei; Baoshan He; Liying Jiang; Xiaoxia Sun; Huali Jin (Analytica Chimica Acta, 2023)

Determination of potential thresholds for N-ethyl-N-nitrosourea and ethyl methanesulfonate based on a multi-endpoint genotoxicity assessment platform in rats - Xuejiao Zhu; Jiao Huo; Zhu Zeng; Yunjie Liu; Ruirui Li; Yiyi Chen; Lishi Zhang; Jinyao Chen (Environmental Science and Pollution Research, 2022)
The main goal of the study was to investigate the genotoxic response of N-ethyl-N-nitrosourea (ENU) and ethyl methanesulfonate (EMS) at low doses in a multi-endpoint genotoxicity assessment platform in rats and to derive potential thresholds and related metrics. Male Sprague–Dawley rats were treated by daily oral gavage for 28 consecutive days with ENU (0.25 ~ 8 mg/kg bw) and EMS (5 ~ 160 mg/kg bw), both with six closely spaced dose levels. Pig-a gene mutation assay, micronucleus test, and comet assay were performed in several timepoints. Then, the dose–response relationships were analyzed for possible points of departure (PoD) using the no observed genotoxic effect level and benchmark dose (BMD) protocols with different critical effect sizes (CES, 0.05, 0.1, 0.5, and 1SD). Overall, dose-dependent increases in all investigated endpoints were found for ENU and EMS. PoDs varied across genetic endpoints, timepoints, and statistical methods, and selecting an appropriate lower 95% confidence limit of BMD needs a comprehensive consideration of the mode of action of chemicals, the characteristics of tests, and the model fitting methods. Under the experimental conditions, the PoDs of ENU and EMS were 0.0036 mg/kg bw and 1.7 mg/kg bw, respectively.

Monitoring of Air Pollution by Remote Sensing in Lanzhou City from 2010 to 2019 - Tianzhen Ju; Zhuohong Liang; Wenjun Liu; Bingnan Li; Ruirui Huang; Tunyang Geng (Water, Air, & Soil Pollution, 2022)

sVCAM1 in the Hippocampus Contributes to Postoperative Cognitive Dysfunction in Mice by Inducing Microglial Activation Through the VLA-4 Receptor - Chenglong Li; Qi Li; Shuai Liu; Jiaying Li; Wei Yu; Yan Li; Ruirui Zhang; Sihua Qi (Molecular Neurobiology, 2022)

Reshaping of the soil microbiome by the expansion of invasive plants: shifts in structure, diversity, co-occurrence, niche breadth, and assembly processes - Changchao Li; Huaizhi Bo; Bingzhong Song; Xiaocui Chen; Qingqing Cao; Ruirui Yang; Shuping Ji; Lifei Wang; Jian Liu (Plant and Soil, 2022)

Barley yellow dwarf virus-infected wheat plant modulated selection behavior of vector aphids - Zuqing Hu; Ruirui Chai; Xin Liu; Yao Dong; Dan Su; Nicolas Desneux; Xiaoling Tan; Chen Luo (Journal of Pest Science, 2022)

Apigenin inhibits growth of melanoma by suppressing miR-512-3p and promoting the G1 phase of cell cycle involving the p27 Kip1 protein - Qun Xie; Ruirui Zhang; Dandan Liu; Jing Yang; Qiang Hu; Chao Shan; Xiaohan Li (Molecular and Cellular Biochemistry, 2022)

PLC1 and H2O2 Mediated the Allelopathic Effect of Oridonin on Root Growth in Arabidopsis thaliana - Yue Zhang; Yanhuang An; Ning Yang; Wei Wang; Ruirui Liu; Run Gao; Yaping Zhou (Journal of Plant Growth Regulation, 2022)

Predicting acupuncture efficacy for functional dyspepsia based on routine clinical features: a machine learning study in the framework of predictive, preventive, and personalized medicine - Tao Yin; Hui Zheng; Tingting Ma; Xiaoping Tian; Jing Xu; Ying Li; Lei Lan; Mailan Liu; Ruirui Sun; Yong Tang; Fanrong Liang; Fang Zeng (EPMA Journal, 2022)

Spatiotemporal variations and pollution sources of HCHO over Jiangsu-Zhejiang-Shanghai based on OMI - Tianzhen Ju; Jiachen Fan; Xin Liu; Yulin Li; Jiale Duan; Ruirui Huang; Tunyang Geng; Zhuohong Liang (Air Quality, Atmosphere & Health, 2022)

The content, composition, and influencing factors of organic carbon in the sediments of two types of constructed wetlands - Ruirui Yang; Jiaohui Fang; Qingqing Cao; Di Zhao; Junyu Dong; Renqing Wang; Jian Liu (Environmental Science and Pollution Research, 2021)

Construction of high density genetic map and QTL mapping in sorghum × sudangrass - Peng Jin; Lihua Wang; Wenjie Zhao; Jian Zheng; Yi-Hong Wang; Yanlong Liu; Ruirui Meng; Jichao Dai; Lei Zhou; Jieqin Li (Euphytica, 2021)

Design of supercontinuum laser hyperspectral light detection and ranging (LiDAR) (SCLaHS LiDAR) - Guoqing Zhou; Xiang Zhou; Youjian Song; Donghui Xie; Long Wang; Guangjian Yan; Minglie Hu; Bowen Liu; Weidong Shang; Chenghu Gong; Cheng Wang; Huaguo Huang; et al. (International Journal of Remote Sensing, 2021)

The participation of basolateral amygdala in the efficacy of acupuncture with deqi treating for functional dyspepsia - Ruirui Sun; Zhaoxuan He; Peihong Ma; Shuai Yin; Tao Yin; Xiaoyan Liu; Jin Lu; Yuzhu Qu; Tingting Zhang; Liuyang Huang; Xueling Suo; Du Lei; et al. (Brain Imaging and Behavior, 2021)

Balanced stochastic versus deterministic assembly processes benefit diverse yet uneven ecosystem functions in representative agroecosystems - Wenjing Liu; Emily B. Graham; Yang Dong; Linghao Zhong; Jianwei Zhang; Chongwen Qiu; Ruirui Chen; Xiangui Lin; Youzhi Feng (Environmental Microbiology, 2021)
Summary Ecological assembly processes, by influencing community composition, determine ecosystem functions of microbiomes. However, debate remains on how stochastic versus deterministic assembly processes influence ecosystem functions such as carbon and nutrient cycling. Towards a better understanding, we investigated three types of agroecosystems (the upland, paddy, and flooded) that represent a gradient of stochastic versus deterministic assembly processes. Carbon and nutrient cycling multifunctionality, characterized by nine enzymes associated with soil carbon, nitrogen, phosphorous and sulfur cycling, was evaluated and then associated with microbial assembly processes and co‐occurrence patterns of vital ecological groups. Our results suggest that strong deterministic processes favour microorganisms with convergent functions (as in the upland agroecosystem), while stochasticity‐dominated processes lead to divergent functions (as in the flooded agroecosystem). To benefit agroecosystems services, we speculate that it is critical for a system to maintain balance between its stochastic and deterministic assembly processes (as in the paddy agroecosystem). By doing so, the system can preserve a diverse array of functional traits and also allow for particular traits to flourish. To further confirm this speculation, it is necessary to develop a systematic knowledge beyond merely characterizing general patterns towards the associations among community assembly, composition, and ecosystem functions.

Factors controlling organic carbon distributions in a riverine wetland - Junyu Dong; Di Zhao; Chao Zhang; Qingqing Cao; Jiaohui Fang; Ruirui Yang; Shuping Ji; Changchao Li; Ruiqi Zhao; Jian Liu (Environmental Science and Pollution Research, 2020)

Analysis of pituitary transcriptomics indicates that lncRNAs are involved in the regulation of sheep estrus - Xiaoyue Li; Cunyuan Li; Yueren Xu; Rui Yao; Huixiang Li; Wei Ni; Renzhe Quan; Mengdan Zhang; Li Liu; Shuting Yu; Yaseen Ullah; Ruirui Hu; et al. (Functional & Integrative Genomics, 2020)

Differences of the microbial community structures and predicted metabolic potentials in the lake, river, and wetland sediments in Dongping Lake Basin - Jiaohui Fang; Ruirui Yang; Qingqing Cao; Junyu Dong; Changchao Li; Quan Quan; Miansong Huang; Jian Liu (Environmental Science and Pollution Research, 2020)

A mechanical method for predicting TBM penetration rates - Ruirui Wang; Xu Guo; Jianbin Li; Jian Wang; Liujie Jing; Zhengyu Liu; Xinji Xu (Arabian Journal of Geosciences, 2020)

Effects of different inhibitors such as malonic acid, Na3PO4 and HgCl2 on uptake of different forms of antimony in rice plant - RenWei Feng; Lei Lei; BiXiu Liu; WenXiang Chen; RuiRui Zhang; LiZhen Wang; YuanPing Li; JunMing Su; JiaXin Dai; RenJie Wang; ZiTing Lin; Ibtissem Ben Fekih; et al. (Plant and Soil, 2019)

Source apportionment and health risk assessment of trace elements in the heavy industry areas of Tangshan, China - Ruirui Si; Jinyuan Xin; Wenyu Zhang; Shihong Li; Tianxue Wen; Yuesi Wang; Yining Ma; Zirui Liu; Xiaojuan Xu; Miaoling Li; Guangjing Liu (Air Quality, Atmosphere & Health, 2019)

ABA signaling rather than ABA metabolism is involved in trehalose-induced drought tolerance in tomato plants - Wenqing Yu; Ruirui Zhao; Liu Wang; Shujuan Zhang; Rui Li; Jiping Sheng; Lin Shen (Planta, 2019)

Ghrelin Promotes Cortical Neurites Growth in Late Stage After Oxygen-Glucose Deprivation/Reperfusion Injury - Jing Liu; Man Chen; Ruirui Dong; Changwei Sun; Shuo Li; Shigong Zhu (Journal of Molecular Neuroscience, 2019)

A biophysical probe on the binding of 2-mercaptothioazoline to bovine hemoglobin - Luyi Zou; Xiaoyue Zhang; Mingying Shao; Ruirui Sun; Yuting Zhu; Binbin Zou; Zhenxing Huang; He Liu; Yue Teng (Environmental Science and Pollution Research, 2019)

Mapping daily leaf area index at 30 m resolution over a meadow steppe area by fusing Landsat, Sentinel-2A and MODIS data - Zhenwang Li; Chengquan Huang; Zhiliang Zhu; Feng Gao; Huan Tang; Xiaoping Xin; Lei Ding; Beibei Shen; Jinxun Liu; Baorui Chen; Xu Wang; Ruirui Yan (International Journal of Remote Sensing, 2018)

Insight into Bacterial Community Diversity and Monthly Fluctuations of Medicago sativa Rhizosphere Soil in Response to Hydrogen Gas Using Illumina High-Throughput Sequencing - Zhiying Li; Xin Liu; Ruirui Liu; Lulu Li; Lin Wang; Weiwei Wang (Current Microbiology, 2018)

The Dysfunction of the Cerebellum and Its Cerebellum-Reward-Sensorimotor Loops in Chronic Spontaneous Urticaria - Yuming Wang; Jiliang Fang; Ping Song; Yan Bao; Wenwen Song; Jiao Liu; Courtney Lang; Kristen Jorgenson; Minyoung Jung; Dong Shen; Shasha Li; Ruirui Sun; et al. (The Cerebellum, 2018)

Enhanced drought tolerance in tomato plants by overexpression of SlMAPK1 - Liu Wang; Ruirui Zhao; Rui Li; Wenqing Yu; Meijing Yang; Jiping Sheng; Lin Shen (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

A comparison of amorphous calcium carbonate crystallization in aqueous solutions of MgCl2 and MgSO4: implications for paleo-ocean chemistry - Mei Han; Yanyang Zhao; Hui Zhao; Zuozhen Han; Huaxiao Yan; Bin Sun; Ruirui Meng; Dingxiang Zhuang; Dan Li; Binwei Liu (Mineralogy and Petrology, 2018)

Facilitation or Competition? The Effects of the Shrub Species Tamarix chinensis on Herbaceous Communities are Dependent on the Successional Stage in an Impacted Coastal Wetland of North China - Ning Du; Pan Wu; Franziska Eller; Dayou Zhou; Jian Liu; Wenhao Gan; Ruirui Yang; Min Dai; Yandong Chen; Renqing Wang; Weihua Guo (Wetlands, 2017)

MiR-340 Regulates Fibrinolysis and Axon Regrowth Following Sciatic Nerve Injury - Shiying Li; Ruirui Zhang; Ying Yuan; Sheng Yi; Qianqian Chen; Leilei Gong; Jie Liu; Fei Ding; Zheng Cao; Xiaosong Gu (Molecular Neurobiology, 2017)

Global identification and expression analysis of stress-responsive genes of the Argonaute family in apple - Ruirui Xu; Caiyun Liu; Ning Li; Shizhong Zhang (Molecular Genetics and Genomics, 2016)

Feasibility of human hair follicle-derived mesenchymal stem cells/CultiSpher®-G constructs in regenerative medicine - Pengdong Li; Feilin Liu; Chunling Wu; Wenyue Jiang; Guifang Zhao; Li Liu; Tingting Bai; Li Wang; Yixu Jiang; Lili Guo; Xiaojuan Qi; Junna Kou; et al. (Cell and Tissue Research, 2015)

Study the Toxicity to Microcystis aeruginosa Induced by TiO2 Nanoparticles Photocatalysis Under UV Light - Ruirui Lu; Peng Liu; Xiaojuan Chen (Bulletin of Environmental Contamination and Toxicology, 2015)

Association study of a common genetic variant in pre-miR-1596 with chicken performance traits - Hong Li; Yadong Tian; Guirong Sun; Xiaojun Liu; Ruirui Jiang; Ruili Han; Guoxi Li; Xiangtao Kang (Molecular Biology Reports, 2014)

Study on the Fragmentation Pathway of the Aconitine-Type Alkaloids under Electrospray Ionization Tandem Mass Spectrometry Utilizing Quantum Chemistry - Xin Chen; Peng Tan; Ruirui He; Yong-gang Liu (Journal of Pharmaceutical Innovation, 2013)

Estimation of groundwater residence time and recession rate in watershed of the Loess Plateau - Ruirui Zhu; Hongxing Zheng; Changming Liu (Journal of Geographical Sciences, 2010)

Phylogeographic analyses suggest that a deciduous species ( Ostryopsis davidiana Decne., Betulaceae) survived in northern China during the Last Glacial Maximum - Bin Tian; Ruirui Liu; Liuyang Wang; Qiang Qiu; Kangming Chen; Jianquan Liu (Journal of Biogeography, 2009)
Aim Palaeontologial data suggest that all temperate forest species in northern China migrated southwards during the Last Glacial Maximum (LGM) and recolonized post‐glacially within the Holocene. We tested this assumption using phylogeographical studies of a temperate deciduous shrub species ( Ostryopsis davidiana Decne., Betulaceae), which has a wide distribution in northern China. Location Northern China. Methods We sequenced two chloroplast DNA (cpDNA) fragments ( trn L –trn F and psb A –trn H, together about 1300 bp in length) of 294 plants from 21 populations across the total distribution range of this species. We used maximum parsimony and haplotype network methods to construct phylogenetic relationships among haplotypes. Results The analysis of cpDNA variation identified eight haplotypes. A single haplotype was fixed in all populations except for one population that was polymorphic, having two haplotypes. The population subdivisions were extremely high ( G ST = 0.972 and N ST = 0.974), suggesting very low gene flow between populations. Haplotypes clustered into two tentative clades, both of which occur in the southern region of the species’ range but only one of which occurs in the northern region. Across the sampled populations, the haplotype distributions were differentiated geographically. Main conclusions Our analyses suggest that multiple refugia were maintained across the range of O. davidiana in both northern (north of the Qing Mountains) and southern (south of the Qing Mountains) regions during the LGM rather than that the species survived only in the south and subsequently colonized northwards. The extremely low within‐population diversity of this species suggests strong bottleneck or founder effects within each fragmented region during the Quaternary climatic oscillations. These findings provide important clues for understanding range shifts and changes in within‐ and/or between‐population genetic diversity of temperate forests in response to past climatic oscillations in northern China.